Health care for homosexual women: discourses of Primary Health Care nurses - Bezerra, Thalia Albuquerque; Alves, Beatriz Pereira; Barbalho, Isabela Lunara Alves; Sousa, Jonathan Pereira de; Adriano, Anna Kalyne César Grangeiro; Fernandes, Petra Kelly Rabelo de Sousa; Fernandes, Marcelo Costa (O Mundo da Saúde, 2023)
Healthcare is still a difficult issue to handle for the homosexual population, sometimes it is apparent that nurses are unprepared in providing care directed at issues related to the sexual orientation of women included in this group, implying that all women are heterosexual. Thus, the present study aimed to analyze the nursing care offered to homosexual women in primary health care from the nurse’s perspective. This is a qualitative study of a descriptive nature, carried out with thirteen nurses working in Primary Care in a city in the interior of the state of Paraiba, Northeastern Brazil. Data collection took place between June and July 2020, through semi-structured interviews, and analyzed using the Collective Subject Discourse technique. The statements were synthesized into three categories: 1) Nursing care for homosexual women; 2) Weaknesses in the care plan: from equality to fairness; and 3) Limitations in knowledge about public health policies for homosexual women. Among the perceptions identified, we highlight the performance of care without direction, the non-recognition of specific healthcare needs, as well as the nurses’ lack of knowledge about public policies involving homosexual women.